Basic Research in Endocrinology A Modern Strategy for the Development and Technologies of Personalized Medicine - Voevoda, Mikhail Ivanovich; Ragino, Yuliya I. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The first all-Russia conference with international participation "Basic Research in Endocrinology: A Modern Strategy for the Development and Technologies of Personalized Medicine" was held in Novosibirsk on 26-27 November 2020. The purpose of this conference was to disseminate the latest basic and clinical findings in the fields of etiology, clinical characteristics, and modern diagnostics and treatments of endocrine disorders among various relevant specialists. The conference was intended for practicing endocrinologists, primary care physicians, medical geneticists, pediatric endocrinologists, pediatricians, and physician-scientists. The main topics included epidemiology and pathogenesis of endocrine disorders; genomic research in endocrinology; biochemical characteristics of endocrine aberrations; immunology and immunogenetics in endocrinology; cellular technologies in endocrinology; metabolomic research in endocrinology; pharmacogenetics; basic pathomorphology; high-tech care of patients with endocrine disorders; iodine-deficiency-related, autoimmune, and oncological diseases of the thyroid; modern diagnostic and therapeutic strategies for diabetes mellitus; osteoporosis and osteopenias; polyendocrinopathies; an interdisciplinary approach to the diagnosis and treatment of obesity and metabolic syndrome; hypo- and hyperparathyroidism, vitamin D; neuroendocrine disorders; reproductive health; rehabilitation of patients with endocrine disorders; health resort and spa treatments of endocrine disorders and comorbid conditions.